An Enzymatic 2‐Step Cofactor and Co‐Product Recycling Cascade towards a Chiral 1, 2‐Diol. Part I: Cascade Design. Issue 11 (14th May 2019) - Kulig, Justyna; Sehl, Torsten; Mackfeld, Ursula; Wiechert, Wolfgang; Pohl, Martina; Rother, Dörte
Abstract: Alcohol dehydrogenases are of high interest for stereoselective syntheses of chiral building blocks such as 1, 2‐diols. As this class of enzymes requires nicotinamide cofactors, their application in biotechnological synthesis reactions is economically only feasible with appropriate cofactor regeneration. Therefore, a co‐substrate is oxidized to the respective co‐product that accumulates in equal concentration to the desired target product. Co‐product removal during the course of the reaction shifts the reaction towards formation of the target product and minimizes undesired side effects. Here we describe an atom efficient enzymatic cofactor regeneration system where the co‐product of the ADH is recycled as a substrate in another reaction set. A 2‐step enzymatic cascade consisting of a thiamine diphosphate (ThDP)‐dependent carboligase and an alcohol dehydrogenase is presented here as a model reaction. In the first step benzaldehyde and acetaldehyde react to a chiral 2‐hydroxy ketone, which is subsequently reduced by to a 1, 2‐diol. By choice of an appropriate co‐substrate (here: benzyl alcohol) for the cofactor regeneration in the alcohol dehydrogenases (ADH)‐catalyzed step, the co‐product (here: benzaldehyde) can be used as a substrate for the carboligation step. Even without any addition of benzaldehyde in the first reaction step, this cascade design yielded 1, 2‐diol concentrations of >100 mM with optical purities ( ee, de ) of up to 99%. Moreover, this approach overcomes the low benzaldehyde solubility in aqueous systems and optimizes the atom economy of the reaction by reduced waste production. The example presented here for the 2‐step recycling cascade of (1 R, 2 R )‐1‐phenylpropane‐1, 2‐diol can be applied for any set of enzymes, where the co‐products of one process step serve as substrates for a coupled reaction. Abstract :